Thermal performance for electromagnetohydrodynamic flow of non-Newtonian Casson fluid through porous microtube - Reza, Motahar; Rana, Amalendu; Patra, Raghunath (International Journal of Engineering and Technology, 2020)
A theoretical investigation is done to analyze the heat transfer features of non-Newtonian Casson fluid in a porous microtube with electro kinetic effects associated with the applied magnetic field. The exact analytical solutions the velocity and temperature profiles of non-Newtonian Casson fluid in porous micro-tube related to combining effects of electromagnetohydrodynamics forces and electrokinetic forces have been obtained using a variation of parameter. Temperature and flow distribution characteristics of Casson fluid flow are controlled by the obtruded pressure-gradients, applied a magnetic field and electro-kinetic forces. The exciting features of the electromagnetohydrodynamics flow along with the features of the heat flow rate are examined by variation in the non-dimensional physical arguments on velocity and temperature functions. The effect of the Casson parameter on the velocity and temperature profiles has been investigated analyzed. The fluid flow rate and the heat transfer rate of Casson fluid within porous micro-tube is controlled by the strength applied electric and magnetic field.Â